Effect of Birth Asphyxia on Newborn Infant at Al Zahraa Teaching Hospital (2024-2025) - Alsaheb, Ali Ayad Abd; Al-Obaidi, Aida H.H.; Yacob, Hawraa S.; Zgher, Zainab I.; Muzail, Asmaa A. (American Journal of Biology and Natural Sciences, 2026)
Birth asphyxia is a major cause of neonatal morbidity and mortality on a global scale especially in low and middle income countries. It is due to the inability to begin and maintain proper breathing during birth and cause hypoxic-ischemic damage and possible neurological disability in the long-term. Intrauterine asphyxia means the insufficient supply of oxygen to the fetus in the womb before or at the birth and results in hypoxia and acidosis. The purpose of this study was to test the impact of birth asphyxia among the newborns admitted to Al-Zahraa Teaching Hospital, in terms of clinical presentation, complications, lab results, and short-term outcomes during the period from January (2024) to June (2025) and compromised 31 newborn infants with full maternal and neonatal data. Birth asphyxia was used as a definition of Apgar score of less than 7 at 5 minutes. Motherly features, medical history, neonatal clinical records (Sarnat stage, seizures), laboratory study including random blood sugar (RBS), urea, creatinine and calcium, period of stay and outcome were documented. The findings revealed that 41.9% of study individuals were asphyxiated; in which, maternal age shown insignificant variation with non-asphyxiated ones but a significant difference in parity and gravidity. Among the past maternal medical history, diabetes and hypertension were elevated significantly in asphyxiated individuals compared to non-asphyxiated ones; while among mothers of asphyxiated neonates, diabetes was more frequently. In Sarnat stage, asphyxiated individuals reported a reduction in none and mild but an elevation elevation in moderate and severe cases when compared to non-asphyxiated data. Subsequently, data observed a higher rate of moderate cases compared to severe mild and none. Iincidence of seizures was increased significantly in asphyxiated individuals compared to non-asphyxias. Length of NICU and hospital stay identified no marked differences between the asphyxiated and non-asphyxiated group. Data of serum markers detected that asphyxiated cases having a significant lowering in RBS and calcium with higher creatinine but no marked alteration in urea compared to non-asphyxiated group. The findings of short term outcome reported a significant increase in died neonates compared to alive which in contrast to non-asphyxiated cases that shown the lack of mortalities.